List of authorized private school courses. - Philippines (Republic). Bureau of Private Schools ([Manila [s.n.], 1911)
Annual.
Supplement no.1, 1953 bound with 1953.
Supplementary lists issued from time to time.
Title slightly varies.
Keywords: Private schools -- Curricula. -- Philippines